KASUS KEPERCAYAAN DIRI PADA SISWA YANG MENGIKUTI KOMUNITAS CHEERLEADERS LATAR LAYANAN KOMUNITAS DI KOTA MALANG - Wahyu Adi Candra; Amanda Pasca Rini (Jurnal Riset Multidisiplin Edukasi, 2025)
Self-confidence is a crucial psychological aspect that supports individual performance, particularly in sports and performing arts activities that require public appearance, such as cheerleading. This study aimed to identify self-confidence issues among cheerleading community members and to design and evaluate an appropriate psychological intervention within a community service context. The study employed a qualitative approach with a case study design involving the Stetsa Cheerleaders Squad (SCS) in Malang City. The participants were cheerleading members aged 16–18 years who exhibited low to moderate levels of self-confidence. Data were collected using a multimethod assessment approach, including non-participant observation, semi-structured interviews with the coach, Focus Group Discussions (FGD), and a self-confidence scale based on Lauster’s theory. The assessment results indicated that several members experienced low self-confidence, characterized by performance anxiety, self-doubt, avoidance behavior, and difficulties in emotional regulation during training and competitions. The Cognitive Behavior Therapy (CBT)-based intervention was found to be effective in helping members identify and modify negative thought patterns, increase performance confidence, and enhance mental readiness. This study highlights the importance of community-based psychological services in supporting psychological development and optimal performance among cheerleading members.